Penerapan Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) dalam Penentuan Menu Terfavorit di Sero Caffe - Pasrah Surya Babega; Hari Marfalino (Jurnal Sains Informatika Terapan, 2026)
This study discusses the application of the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method in a mobile-based Decision Support System to determine the most favorite menu at Sero Caffe. The problem faced is that the process of determining the best menu is still subjective and has not been supported by structured data analysis. This study aims to design a system that can assist management in making objective decisions based on several evaluation criteria, namely taste, price, popularity, and health. The data were obtained from customer evaluations of the available menus and then processed using the MOORA method stages, including the construction of the decision matrix, normalization, weighting, and ranking of alternatives. The results show that the developed decision support system is able to provide accurate and systematic recommendations for the most favorite menu, thereby improving the effectiveness of decision making and supporting business strategy development at Sero Caffe.